Measuring market-sensing capabilities for new product development success - Dias, Á. L.; Lages, L. F. (Journal of Small Business and Enterprise Development, 2021)
The purpose of this paper is to conceptualize and operationalize the concept of sensing capabilities and analyse its relationship with new product development (NPD) success and organic organizational structures. To our knowledge, past measures of market sensing capabilities have never included opportunity interpretation, through business experience and organizational articulation, as part of the concept. Based on a sample of over 180 SMEs, market sensing capabilities constructs and their relationships were tested through academics’ and managers’ perceptions. The measure was tested using confirmatory factor analysis. Findings reveal theoretically sound constructs based on four underlying sensing capabilities components: analytical processes, customer relationship, business experience, and organizational articulation. Results demonstrate reliability, convergent, discriminant, and nomological validity. All four dimensions are positively associated with new product development success and are more likely to appear in organic organizational structures. The resulting instrument provides managers with a valuable tool to measure firms’ abilities to address environmental uncertainty. By using this instrument, managers can assess internal organizational structures and resources allocated to sensing capabilities. By developing sensing capabilities, managers might ultimately influence their new product development strategy. Findings also reveal that sensing capabilities are positively and significantly associated with organic organizational structures. Existing sensing capabilities measures are focused on environmental scanning, and the essence of the concept is not fully expressed by the traditional measures of analytical processes and customer relationship. Our new measure includes opportunity interpretation through business experience and organizational articulation.